Trade openness and economic growth volatility: An empirical investigation - Kwame Mireku; Ellen Animah Agyei; Daniel Domeher (Cogent Economics & Finance, 2017)
This paper investigated the impact of trade openness on economic growth volatility of Ghana from 1970 to 2013, using cointegration and error correction techniques. Our findings show that both the long and short run economic growth volatility is positively influenced by changes in trade openness. Volatility in domestic credit to private sector, shocks after the economic liberalization and financial openness contributed negative to economic growth volatility in the short run. The major policy implication of our paper is that developing economies should take into consideration their own realities in their trade policies to limit economic growth volatility.